Progression of myopia among medical students: A one-year cohort study - Agung Nugroho; Mohammad Eko Prayogo; Widyandana Widyandana; Sagung Indrawati; Suhardjo Suhardjo (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2020)
Myopia is a common refractive disorder in literate countries related to educationand higher occupational groups. External factors affecting myopia and its progression remainquestionable. Myopia onset and progression occur during childhood and teenager. This studyaimed to determine the progression of myopia and its associated factors in the medical studentof Faculty of Medicine UGM, Yogyakarta, Indonesia, through a one-year cohort study. An initialobservational and cross-sectional survey conducted as baseline data. Correlation calculatedusing Chi-square and the Spearman correlation coefficient analysis. A longitudinal cohortstudy conducted 12 months later to the initial survey. Myopia determined with an autorefractorwithout cycloplegia. BMI, intraocular pressure, and corneal curvature evaluated as factorsrelated to progression. Five hundred five students (98%; 505 of 515; 317 from the school ofmedicine (SoM), 188 from the school of nursing and nutrition (SoNN)) age 15-20 years wereexamined. Prevalence of myopia among SoM students was 69.4% (n=220 of 317) and 41.4%(n=78 of 188) in SoNN. Myopia (SER ≥-0.5 D) found in 298 students, 81 boys (27.2%) and 217girls (72.8%). Chi-square test revealed that myopia more common in Chinese than Javaneseand other (p=0.006) but a similar proportion in gender (p = 0.785) and age (p=0.369). Theaverage change of myopic progression was -0.401 D and -0.094 D per year in SoM and SoNN,respectively (p = 0.000). The average change of myopia of boys and girls was -0.138 D and-0.117 D, respectively (p = 0.871). There was no statistically significant correlation betweensubjective refraction change and factors related to progression. The progression of myopia inYogyakarta relatively similar to Western countries. Progression in the school of medicine washigher than the school of nursing and nutrition, but similar between boys and girls. No relatedfactor correlated with the progression of myopia expects further studies.